2009
DOI: 10.1016/j.revpalbo.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Determining the absolute abundance of dinoflagellate cysts in recent marine sediments: The Lycopodium marker-grain method put to the test

Abstract: Absolute abundances (concentrations) of dinoflagellate cysts are often determined through the addition of Lycopodium clavatum marker-grains as a spike to a sample before palynological processing. An interlaboratory calibration exercise was set up in order to test the comparability of results obtained in different laboratories, each using its own preparation method. Each of the 23 laboratories received the same amount of homogenized splits of four Quaternary sediment samples. The samples originate from differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 157 publications
(85 citation statements)
references
References 27 publications
1
83
1
Order By: Relevance
“…This produces fairly uniform fossil assemblages with greatly reduced AOM concentrations, although scanning over many remaining AOM fragments was necessary to achieve sufficient specimen counts. Single Lycopodium tablets were added to samples after laboratory oxidation for absolute quantification of palynomorphs (counts per gram; Mertens et al, 2009). Previous experiments have shown that the oxidation required to liberate palynomorphs from AOM destroys a large proportion of Lycopodium spores if they are added prior to oxidation.…”
Section: Palynological Methodsmentioning
confidence: 99%
“…This produces fairly uniform fossil assemblages with greatly reduced AOM concentrations, although scanning over many remaining AOM fragments was necessary to achieve sufficient specimen counts. Single Lycopodium tablets were added to samples after laboratory oxidation for absolute quantification of palynomorphs (counts per gram; Mertens et al, 2009). Previous experiments have shown that the oxidation required to liberate palynomorphs from AOM destroys a large proportion of Lycopodium spores if they are added prior to oxidation.…”
Section: Palynological Methodsmentioning
confidence: 99%
“…To facilitate quantitative analyses single Lycopodium tablets (Lund University, Batch No. 1031) were added to samples after laboratory oxidation (Mertens et al, 2009). Absolute abundances (specimens per gram) of the various components of the palynofacies and dinoflagellate cysts (dinocyst) assemblages were calculated after Stockmarr (1971) and Mertens et al (2009).…”
Section: Palynologymentioning
confidence: 99%
“…Most of the KWIS studies hypothesized that the driving mechanisms for deposition of rhythmically bedded strata were climate-controlled variations in i) primary productivity (productivity model); ii) input of terrigeneous sediments (dilution model); iii) the intensity of bottom currents (scour model); and iv) benthic oxygenation and hence, the extent and preservation of organic matter (redox model). More recently, spectral analyses of geochemical, lithological and paleobiological data have provided quantitative evidence for the existence of primary astronomic forcing signal in Cenomanian and Turonian sequences of the KWIS, suggesting that, despite warm equitable climates of the greenhouse world during that time, climate responded to changes in solar insolation driven by Milankovitch cycles (Sageman et al, 1997(Sageman et al, , 1998Meyers et al, 2001). In particular, these authors concluded that a combination of astronomic cycles were responsible for the rhythmic strata of the Bridge Creek Limestone Member and hypothesized that the obliquity cycle, through its influence on high-latitude precipitation, was the primary factor responsible for dilution of the carbonate sedimentation by detrital material and that the precession cycle, through its influence on evaporation and upwelling in the southern part of the KWIS, enhanced carbonate productivity.…”
Section: Introductionmentioning
confidence: 99%
“…One calibrated tablet of Lycopodium clavatum (batch no. 3862, produced and distributed by the Department of Quaternary Geology, University of Lund, Sweden) was added to 25 each sample in order to estimate palynomorph concentrations (Stockmarr, 1971;Mertens et al, 2009bMertens et al, , 2012. Samples were treated with room temperature 10% HCl to remove carbonates.…”
Section: Palynological Preparationmentioning
confidence: 99%